Methodological possibilities for determining the ecological network - Kutnyánszky, Virág; Szilvácsku, Miklós Zsolt (4D Journal of Landscape Architecture and Garden Art, 2025)
An ecological network as a biodiversity and habitat conservation tool, maintaining the material and energy cycle, is a coherent system of natural and semi-natural landscape elements. It can be divided into three basic structural units: core areas, ecological corridors and buffer zones, which are sometimes supplemented by rehabilitation areas. Our research on planning methods and definition of the ecological network has revealed different approaches and influencing factors. We have identified that a network can aim to improve the living conditions of a species (or group of species), or it can aim to improve overall ecological condition and connectivity, and reduce fragmentation. A network (and thus its planning) is influenced by four factors: natural attributes and the processes that take place within the landscape provide a framework; wildlife as a user is a dominant; and humans have a shaping influence on the network. Along these lines, we have presented a wide range of tools, from decision-based stakeholder-driven planning, through landscape metric analysis, to connectivity models based on graph theory. Ecological network planning, which started around 1980, is very different from the methods used today, as the spread of available technologies (mainly GIS technology) and software allows us to integrate an increasing number of aspects into the network modelling, producing objective results. However, it can be stated that models based on increasingly complex calculations have moved away from a planning perspective; they are not intended to fit legal or spatial planning conditions, but they do provide a basis for small-scale network development, e.g. the creation of wildlife crossings, or the rehabilitation of a corridor or habitat.
Keywords: connectivity; ecological network; fragmentation; habitat suitability; landscape ecology; landscape metrics; gis modelling